Indonesian megaliths : a forgotten cultural heritage - Steimer-Herbet, Tara (Laboratoire d'archéologie préhistorique UNIGE., 2018)
An exploration of Indonesian megaliths based on scientific documents and field visits, this work highlights misunderstood - and sometimes threatened by destruction - aspects of Indonesian cultural heritage and offers a unique perspective on megalithic monuments abandoned for several centuries in the archipelago.